PEMBERIAN MIKROORGANISME LOKAL (MOL) BONGGOL PISANG PADA PENGOMPOSAN JERAMI PADI YANG DIAPLIKASIKAN UNTUK TANAMANPADI SAWAH (Oryza sativa L.) VARIETAS PB-42 DENGAN METODE SRI - Datik Lestari; Nurbaiti '; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to determine the effectiveness and best compound of banana corm local microorganism on rice straw composting forPB-42 riceplant (Oryza sativa L.) with SRI method. This research conducted at the Department of Agrotechnology Greenhouse Faculty of Agriculture, University of Riau in May to November 2013. Completely Randomized Design with 4 treatments and 5 replications used in this experiment. The treatments consisted compound of banana corm local microorganism and water is M1 = 1 :6, M2 = 1 : 5, M3 = 1 : 4, M4 = 1 : 3. Data were analyzed using analysis of varianceand mean separations with Duncan's Multiple Range Test at the 5% level. The parameters measured were the plant height, tillerstotal number, number of productive tillers, panicle emergence time, panicle length, plant dry weight, percentage of fillinggrain, weight of 1000 filled grain and milled dry grain per hill. The results showed that administration of banana corm local microorganism has not significantly affectedto all parameters. The compound of banana corm local microorganism and water of 1:6 dilutionnot significantly affect on growth and yield compare to compost with the relatively higher levels of dilution chemical properties treatments except on panicle emergence time. Keywords : Banana corm local microorganism, rice plant, rice straw compost, SRI method